(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The achievements of our generation sciens and culture for century’s habe had a great impact on the development of science in world culture.The article considers the effective use of our scientific and cultural heritage in the educational sustem as an important factor in raising the ideological potential of youth.